2005
DOI: 10.1007/s00247-005-1419-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of pediatric sickle cell disease patients with abnormal high velocities on transcranial Doppler

Abstract: Cerebral arteriopathy can be detected in children with sickle cell disease (SCD) by transcranial Doppler (TCD). Abnormally high velocities are predictive of high stroke risk, which can be reduced by transfusion therapy. We report the results of the screening of 291 SCD children followed in our center, including the clinical and imaging follow-up of 35 children with abnormal TCDs who were placed on transfusion therapy. We postulated that patients with normal MRA findings and abnormal TCD velocities that normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 14 publications
5
62
2
4
Order By: Relevance
“…10 HU decreased elevated TCD velocities, 11,12 or allowed transfusion to be stopped in some patients who had normalized high velocities upon transfusion therapy. 7 However, in all these studies, a subset of patients did not respond to HU, presenting with a higher rate of stroke recurrence than expected with transfusion therapy, 11,12 or redeveloping high velocities when off transfusion. 7 Multicenter trials are needed to identify a selected SS children population who might be switched from transfusion regimen to HU therapy.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…10 HU decreased elevated TCD velocities, 11,12 or allowed transfusion to be stopped in some patients who had normalized high velocities upon transfusion therapy. 7 However, in all these studies, a subset of patients did not respond to HU, presenting with a higher rate of stroke recurrence than expected with transfusion therapy, 11,12 or redeveloping high velocities when off transfusion. 7 Multicenter trials are needed to identify a selected SS children population who might be switched from transfusion regimen to HU therapy.…”
Section: Resultsmentioning
confidence: 94%
“…7 However, in all these studies, a subset of patients did not respond to HU, presenting with a higher rate of stroke recurrence than expected with transfusion therapy, 11,12 or redeveloping high velocities when off transfusion. 7 Multicenter trials are needed to identify a selected SS children population who might be switched from transfusion regimen to HU therapy. In our series, recurrence of arterial stenosis at the same location was observed in 4 children after discontinuation of transfusion therapy, as previously reported in 2 children.…”
Section: Resultsmentioning
confidence: 94%
“…It is now well-established that androgen treatment is a risk factor for liver abnormalities in both FA and non-FA patients [9][10][11][12][13][14]. Some studies have previously reported hepatic tumors in patients with FA [9,15,16], but little is known concerning other abnormalities of the livers of these patients. Therefore, we aimed to describe for the first time the spectrum of radiological and biological liver abnormalities in a cohort of patients with FA.…”
Section: Methodsmentioning
confidence: 99%
“…The median number of liver laboratory evaluations (LLEs) per patient during follow-up was 3 (range: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], with a median time between the first and last LLE of 3.6 years (range: 1 month to 30 years).…”
Section: Methodsmentioning
confidence: 99%
“…Silent cerebral infarction (SCI) is diagnosed only using magnetic resonance imaging (MRI) in patients with no focal neurological deficit, but is associated with cognitive difficulties [8] that families often report. SCI can develop very early in life, with rates between 11 and 15% in children less than 2 years [9][10][11] and progressive accrual throughout childhood and adolescence [11,12] and into adulthood.…”
Section: Introductionmentioning
confidence: 99%